Маркетингова та логістична діяльність автомобілебудівних підприємств - Терлецька, В. О. (Видавництво Львівської політехніки, 2018)
Досліджено та проаналізовано маркетингову та логістичну діяльності авто- мобілебудівних підприємств для забезпечення на їх основі конкурентних переваг та формування позитивного іміджу в динамічних умовах функціонування. Визначено на що спрямовані маркетингова та логістична діяльності підприємств в Україні. Охарактеризовано ринок автомобілебудівної продукції України. Виокремлено недоліки здійснення маркетингової і логістичної діяльності вітчизняних підприємств. Розглянуто концепцію “точно в строк”, визначено її базові постулати та переваги. Представлено рекомендації для ефективного функціонування маркетингової та логістичної діяльності вітчизняних підприємств автомобілебудування.

The marketing and logistic activities of automobile companies have been investigated and analyzed to provide competitive advantages on their basis and to create a positive image in dynamic conditions. Defined by what exist targeted marketing and logistics activities of enterprises in Ukraine.The market of automotive products of Ukraine has been described. The disadvantages of marketing and logistics activities of domestic enterprises are highlighted. The concept “just-in-time” has been considered, its basic postulates and advantages have been defined. Recommendations for effective functioning of marketing and logistic activity of domestic enterprises of automobile industry have been presented. Ensuring the proper positive image of high-tech domestic automotive companies is possible on the basis of the application of a complex of marketing and logistics communications in the dynamic and changing conditions of changing market conditions. The improvement of communication determinants of marketing and logistics activities enables to build effective market strategies, mechanisms and tools for positioning enterprises in high-tech markets. In the conditions of significant saturation of markets by differentiated commodity products of high concentration and intensity of competition, enterprises achieve competitive advantages at the expense of the image and development of successful technologies for the provision of logistic services, which in the present circumstances plays an important role. Characteristic features of the current state of automobile construction enterprises are the high dynamism and the increasing complexity of interconnections between market participants entering into processes of production, distribution, exchange and consumption. The domestic market for automotive products is characterized by dynamic changes that need to be taken into account in operational and strategic planning. The main reason is the rapidity of scientific and technological progress, the development of information technology, expanding the horizons of market interactions, spreading the boundaries of markets and accelerating the processes of globalization. In the industry, such interpenetration is particularly intense, since motor vehicle manufacturers have the highest mobility and are most sensitive to changes and consumer preferences. Transnational companies, by virtue of their economic power, can influence consumers’ minds both through the reduction of prices for traditional goods, and through constant updating and development of its functional characteristics. And, as today, after-sales service is important for consumers, and the good value for domestic automotive companies is becoming a matter of successful marketing and logistics activities. The guiding idea of this paradigm is to harmonize the interests of the manufacturer, consumer and society as a whole. At the present stage of development, Ukraine is not integrated into the world car industry; there are no modern production of leading world companies in its territory. The main problems of the domestic automobile industry are: the lack of modern technological lines; low scale and level of production localization; unfavorable regulatory environment. The main strengths of the domestic automotive industry are: convenient logistics; availability of trained human resources; unsaturated and growing domestic sales.
Marketing and logistic activities of automotive enterprises
Keywords: логістичні системи; високотехнологічні підприємства; е-логістика; маркетингові комунікації; маркетингові цінності; взаємодія; logistic systems; high-tech enterprises; e-logistics; marketing communications; marketing values; interaction; 658.7.011.1